Sudden unexpected postnatal collapse at 20 hours from birth during skin-to-skin care related to brainstem developmental alterations – a case report - Lavezzi, Anna M.; Piscioli, Francesco; Pusiol, Teresa (Folia Neuropathologica, 2017)
This report describes a case of sudden collapse of a 20-hour-old newborn, while he was placed close to their mother according to skin-to-skin care, attributed to developmental alterations of brainstem nuclei involved in regulation of the vital functions. The infant, after a normal pregnancy, appeared well developed at birth, with no evidence of malformations or trauma, but showing severe asphyxia. The routine autopsy did not reveal a possible cause of death. Only the in-depth anatomopathological examination of the autonomic nervous system, according to the protocol developed by the “Lino Rossi” Research Center of Milan University, provided an explanation of the pathogenetic mechanism of this early death. The sudden death, a few hours after birth, was the unavoidable outcome of a complex of abnormalities of brainstem nuclei, particularly of the Kölliker-Fuse nucleus, an essential structure for eupneic breathing at birth, exacerbated by the prone position implied by the skin-to-skin contact.